Factors Associated With Work-Life Balance of Working Fathers Involved in Small Business Enterprises: Evidence from Kathmandu Valley - Shakya, Rocky Mani; Devkota, Niranjan; Paudel, Udaya Raj; Parajuli, Seeprata (Quest Journal of Management and Social Sciences, 2021)
Background: Work-life balance (WLB) can be considered as the systematic management of three important components like work-life conflict, work-life interference and work-life convergence. Objective: This study tries to examine the work-life balance of the working fathers involved in small business enterprises in Kathmandu valley. Method: Both descriptive and inferential analysis is used in the study which showed various results. The study adopted the descriptive approach. Respondents were sampled from working fathers in small business enterprises in Kathmandu valley. Non probability sampling technique was used to select 405 respondents. The questionnaire was used for data collection. Descriptive as well as inferential statistics were used for data analysis. Result: The study found that age, education level, business trainings and income level has positive significant relationship with work-life balance. The finding of this study shows that satisfaction and motivation towards working fathers is important factors for balancing the work-life and family life. Conclusion and Recommendation: The paper recommends that there should be inclusive climate in the workplace and policies supporting work-life balance should be forwarded.